Performance analysis of photovoltaic systems of two different technologies in a coastal desert climate zone of Chile. (April 2015) - Ferrada, Pablo; Araya, Francisco; Marzo, Aitor; Fuentealba, Edward
Highlights: We studied the performance of PV technologies in a coastal desert zone in Chile. We determined and analyzed the daily performance ratio in a 16 month period. The dust associated to this place produced a fall of the performance ratio. The energy yield differences became larger for summer and smaller for winter. Performance ratio differently reduced for increasing and decreasing temperatures. Abstract: This paper reports on the performance of photovoltaic systems in the coastal zone of Antofagasta, northern Chile. This region is one of the most suitable places in the world for the use of solar energy due to the high solar radiation levels. However, this location is influenced by a coastal desert climate where the environmental effects on solar technologies are not well known. Therefore, we study the performance ratio of photovoltaic systems in a period of 16 months, in which solar radiation and ambient temperature were quantified. The technologies were modules based on amorphous/microcrystalline silicon tandem thin films and mono crystalline silicon solar cells. The global tilted solar irradiation reached mean values of 8.5 kW h/m 2  day in summer and 6 kW h/m 2  day in winter demonstrating the high radiation available here. We analyzed how the performance ratio is influenced by the dust accumulation and the ambient temperature associated to this place. It came out that the difference of energy yield between the technologies became larger for summer and smaller for winter, and that the performance ratio decreased due to the dust accumulation between −0.04%/day up to −0.13%/day for positive ambient temperature gradient, and between −0.13%/day up to −0.18%/day for negative ambient temperature gradient.